Vitamina C no estresse oxidativo induzido pelo H2O2 em queratinócitos humanos cultivados. - Brito, Gabriela Soares Silva [UNIFESP] (2009)
This study aimed to evaluate the effect of vitamin C in cultured human keratinocytes subjected to oxidative stress by hydrogen peroxide. The method is based on the isolation and cultivation of human keratinocytes into four groups: control, vitamin C, H2O2, H2O2 + Vitamin C, keratinocytes were subjected to oxidative stress by H2O2 for two hours. We evaluated the apoptosis and the release of free radicals by flow cytometry, cellular senescence by MTT kit and proliferation by MTT kit. The results showed that hydrogen peroxide increased the apoptosis, cellular senescence by keratinocytes and that vitamin C did not inhibit cellular injury in a significant Polish. The production of free radicals, the group, Vitamin C produced a greater amount when assiociada to H2O2. Thus, we conclude that vitamin C had no effect on antioxidant cultured human keratinocytes.